2016
DOI: 10.1016/j.pbiomolbio.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on cardiac electrical activity between fibroblasts and myocytes

Abstract: Myocardial injuries often lead to fibrotic deposition. This review presents evidence supporting the concept that fibroblasts in the heart electrically couple to myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…It has been reported that myofibroblasts coupled to cardiomyocytes show an increase in Cx43 expression and an associated increase in gap junction formation (21). Cx43-based contact between myofibroblasts and cardiomyocytes is thought to contribute to ectopic activity and arrhythmias (25,47). In the present study, we show a novel Cx43-dependent aspect of myofibroblast behavior that may contribute to heart failure pathology.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It has been reported that myofibroblasts coupled to cardiomyocytes show an increase in Cx43 expression and an associated increase in gap junction formation (21). Cx43-based contact between myofibroblasts and cardiomyocytes is thought to contribute to ectopic activity and arrhythmias (25,47). In the present study, we show a novel Cx43-dependent aspect of myofibroblast behavior that may contribute to heart failure pathology.…”
Section: Discussionsupporting
confidence: 61%
“…Myofibroblasts are known to promote conduction slowing and ectopic activity in cardiac tissue (25,47). As previously shown (41), these arrhythmogenic properties can be suppressed by disruption of a-SMA stress fibers using pharmacological manipulation.…”
Section: Actin Filament-based Modification Of Cx43mentioning
confidence: 90%
“…Nonmyocytes, mainly interstitial and endothelial cells, represent a heterogeneous, dynamic group of nonexcitable cells that outnumber myocytes, although they occupy a smaller volume fraction (2). Whereas paracrine and structural roles of nonmyocytes are wellestablished in the mammalian heart, awareness of their potential role in electrical signal propagation has only started to emerge (3,4).…”
mentioning
confidence: 99%
“…The arrhythmogenic potential of scars that are highly populated with non-excitable cells is dependent on their ability to form a continuous network that is coupled to the surrounding myocardium 26,27 . However, neither the physical substrate that is responsible for coupling between scar tissue and cardiac myocytes 15,28 nor the cellular network present within this tissue have been fully described. We have characterized a non-myocyte cellular network in a 30-day old RV scar through detailed analyses at ultrastructural resolution using SBF-SEM.…”
Section: Resultsmentioning
confidence: 99%
“…We believe significant changes in these parameters are unlikely to be present in the chimeric mice, however their contribution to the changes in the passive electrical properties of the tissue cannot be discounted. In contrast to the uninjured myocardium, the cell populations in the scar have comparatively lower transmembrane conductances 28,49 , therefore a significant contribution of transmembrane conductance changes www.nature.com/scientificreports www.nature.com/scientificreports/ due to Cx43 deletion to the measured passive conduction properties is less likely. Studies have suggested that cardiac conduction may be altered as a result of enhanced mechanosensitive channel activity in response to cardiac injury 50 .…”
Section: Discussionmentioning
confidence: 99%